2018
DOI: 10.1016/j.jsat.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Focus groups to increase the cultural acceptability of a contingency management intervention for American Indian and Alaska Native Communities

Abstract: A CM intervention for alcohol use disorders should be in alignment with existing cultural and community practices such as alcohol abstinence, is more likely to be successful when Elders and community leaders are champions of the intervention, the intervention is compatible with counseling or treatment methodologies, and the intervention provides rewards that are both culturally specific and practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…Nine studies focussed on alcohol dependence or 'alcoholism' (sic) [24,29,56,64,69,[72][73][74][75]. Two studies focused on alcohol use disorders more broadly (severity not specified) [30,31]. No study was found to exclude clients with dependence.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies focussed on alcohol dependence or 'alcoholism' (sic) [24,29,56,64,69,[72][73][74][75]. Two studies focused on alcohol use disorders more broadly (severity not specified) [30,31]. No study was found to exclude clients with dependence.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the remaining 17 studies, a variety of terms were used to describe the nature of the alcohol problem being treated (Table 3). No diagnostic criteria or screening thresholds were provided for the majority (n = 19, 68%) of studies ( [31,54,56,58,60,63,64,66,71], and six were mixed methods (21.5%) [29,30,59,65,67,68].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations